Some theoretical and practical arguments on the science, technology and innovation system of Vietnam in trend of international integration of science and technology - Truong, Dao Thanh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
In this present age, every sector, every country is strongly influenced by science and technology (S&T). S&T has profound impact on the world economy, position location in international relations and all social activities. In their development strategy, countries consider S&T as a means, an objective for socio-economic development, and to consolidate their position in the competitive economic and political struggle. In the context of international integration of S&T, the role of science, technology and innovation system is increasingly emphasized. We do recognize that to build a such successful system, only the task of state management through promulgation of policy mechanisms is not enough. It requires large participation of all components in the system and, above all, high spirit of innovation. Based on theoretical analysis and experience in developing S&T of some countries in the world and taking into account practical conditions of Viet Nam, the authors present some preliminary assessments on existing drawbacks in the S&T and innovation system of Vietnam and then to propose some policy orientations for the S&T system in the future. Code: 15062601